Scar Girl : a novel - Vlahos, Len (Carolrhoda Lab, 2016)
Told as an interview with the successful but increasingly dysfunctional band after they reach the pinnacle of success, the bandmates and friends try to cope with the amputation of Johnny's leg, Cheyenne's pregnancy, and Harry's unrequited love for Chey.